Strategi Pemasaran Beras Organik dalam Meningkatkan Kepercayaan Konsumen di Kabupaten Kolaka - Usman, Edi; Admayanti, Anita; Rahma, Mutiah (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This research was conducted in Puuroda Village, Baula District, Kolaka Regency, Southeast Sulawesi from May to July 2024. Using qualitative methods with interview and observation techniques, this research aims to analyze marketing strategies for organic rice to increase consumer confidence. SWOT analysis is used to identify internal and external factors. The research r esults show that the main strengths of the product include guaranteed quality, certification, and packaging variations. Disadvantages include high price and short shelf life. Opportunities are identified in the use of e-commerce and local collaboration, while threats come from competition with non-organic products and the circulation of false claims. Recommended strategies include the use of digital platforms for consumer education, emphasis on product quality and certification, and production efficiency to maintain price competitiveness.